The effectiveness of education moral intelligence concepts to children through animation, stories, pictures and computer games - Davood Latifi; Yousef Gorji; faezeh taghipour (اخلاق وحیانی)
Mankind needs ethics to reach perfection, but today in countries there is a competition to acquire new technologies. Therefore, it is necessary to provide ways to increase morality by using these technologies. Moral intelligence is not hereditary and it is possible to increase it, and the best time is childhood and should not be neglected. The purpose of this research is to determine the effectiveness of teaching moral intelligence through animation, stories, pictures and computer games on children. Therefore, 100 female students were selected from Isfahan schools and divided into 5 groups (4 experimental groups and one control group). Then using the questionnaire "moral intelligence of Burba children - parent form" the level of moral intelligence of children was checked and after providing education through animation, stories, pictures and computer games, the level of moral intelligence was checked again and after one month the stability of education was evaluated. The findings showed that the compiled educational packages that were transmitted through animation, stories, pictures and computer games have provided the basis for increasing children's moral intelligence; However, by comparing the changes in moral intelligence, it was found that stories and animations have the greatest effect in increasing moral intelligence, and images have a lesser effect than stories and animations, and finally, computer games have the least effect in increasing moral intelligence. with three other experimental groups.